PENILAIAN MUTU ORGANOLEPTIK DAN pH IKAN ROA (Hemirhampus sp.) SEBAGAI BAHAN BAKU IKAN ASAP (Studi Kasus UKM Ikan Roa Asap Desa Bangga, Kecamatan Paguyaman Pantai) - Fadlianto Botutihe (Fakultas Pertanian Universitas Ichsan Gorontalo, 2016)
This study aims to obtain information on the quality of freshness of roa fish or julung-julung used as raw material for smoked fish in Bangga Village, Paguyaman Pantai District. The method used is organoleptic test (scoring test) and pH test using a pH meter. The results of the study showed that the average organoleptic value of fish from all specifications was 8.78, and the average pH value of the 3 samples tested was 6.36. These results address the organoleptic quality and pH of the roa fish as raw material for smoked fish is still relatively fresh.